Patients Hospitalized in General Wards via the Emergency Department: Early Identification of Predisposing Factors for Death or Unexpected Intensive Care Unit Admission—A Historical Prospective - Thierry Boulain; Isabelle Runge; Nathalie Delorme; Angèle Bouju; Antoine Valéry (Emergency Medicine International)
Background. To identify, upon emergency department (ED) admission, predictors of unexpected death or unplanned intensive care/high dependency units (ICU/HDU) admission during the first 15 days of hospitalization on regular wards. Methods. Prospective cohort study in a medical-surgical adult ED in a teaching hospital, including consecutive patients hospitalized on regular wards after ED visit, and identification of predictors by logistic regression and Cox proportional hazards model. Results. Among 4,619 included patients, 77 (1.67%) target events were observed: 32 unexpected deaths and 45 unplanned transfers to an ICU/HDU. We identified 9 predictors of the target event including the oxygen administration on the ED, unknown current medications, and use of psychoactive drug(s). All predictors put the patients at risk during the first 15 days of hospitalization. A logistic model for hospital mortality prediction (death of all causes) still comprised oxygen administration on the ED, unknown current medications, and the use of psychoactive drug(s) as risk factors. Conclusion. The “use of oxygen therapy on the ED,” the “current use of psychoactive drug(s)”, and the “lack of knowledge of current medications taken by the patients” were important predisposing factors to severe adverse events during the 15 days of hospitalization on regular wards following the ED visit.